TRANSFORMING HEALTHCARE: THE ROLE OF TECHNOLOGY IN MODERN MEDICAL SYSTEMS - A NARRATIVE REVIEW. - Sinha, Suparna; Murugappan, Solai; Sinha, Piyush (Student's Journal of Health Research Africa, 2022)
The realm of digital health seeks to enhance patient care by leveraging technology, such as telemedicine, mobile health applications, and artificial intelligence. The swift incorporation of technology within healthcare systems worldwide has brought about significant transformations in patient care, operational efficiency, and data management. This review aims to consolidate the existing scientific evidence about the influence of several health information technologies on patient safety outcomes. This paper integrates a diverse array of peer-reviewed articles and empirical studies to elucidate the complex impacts of these technologies on the delivery of healthcare. The results highlight that digital technology is vital for improving patient care by increasing accessibility, streamlining operations, and refining diagnostic precision. Nevertheless, ongoing obstacles such as the protection of data privacy, the assurance of interoperability among systems, and the management of implementation expenses remain considerable challenges. This study has implications for future implementations of digital health systems. It provides a foundation for the ongoing adoption and adaptation of the electronic medical record and the assignment of unique identification numbers for each client. Assessing the digital literacy levels of medical professionals to enhance implementation success is a must. Furthermore, when the patient is absent from an interaction, it is crucial for the provider to ascertain the identity of the individual and to be informed of their medical history, including vaccines, pregnancies, and prescriptions.